Automated structural comparisons clarify the phylogeny of the right-hand-shaped polymerases. - Mönttinen, H; Ravantti, J; Stuart, D; Poranen, M (2014)
Polymerases are essential for life, being responsible for replication, transcription, and the repair of nucleic acid molecules. Those that share a right-hand-shaped fold and catalytic site structurally similar to the DNA polymerase I of Escherichia coli may catalyze RNA- or DNA-dependent RNA polymerization, reverse transcription, or DNA replication in eukarya, archaea, bacteria, and their viruses. We have applied novel computational methods for structure-based clustering and phylogenetic analyses of this functionally diverse polymerase superfamily, which currently comprises six families. We identified a structural core common to all right-handed polymerases, composed of 57 amino acid residues, harboring two positionally and chemically conserved residues, the catalytic aspartates. The structural conservation within each of the six families is considerable, for example, the structural core shared by family Y DNA polymerases covers over 90% of the polymerase domain of the Sulfolobus solfataricus Dpo4. Our phylogenetic analyses propose an early separation of RNA-dependent polymerases that use primers from those that are primer-independent. Furthermore, the exchange of polymerase genes between viruses and their hosts is evident. Because of this horizontal gene transfer, the phylogeny of polymerases does not always reflect the evolutionary history of the corresponding organisms.